Psoriasis in resource-limited setting: a case report in a remote area in Indonesia - Pasande, Suspina (International Journal of Research in Medical Sciences, 2022)
The diagnosis and treatment of psoriasis may be challenging in resource-limited setting. We report a 54-year-old male with the diagnosis of psoriasis vulgaris in the rural area of Papua, Indonesia. The diagnosis was made clinically by a general practitioner due to the absence of diagnostics testing and dermatologists around the area. The patient showed improvements after applying combined ointment of glucocorticoids, emollients, and moisturizers.